EKSISTENSI LEMBAGA UNSUR ALIM ULAMA (PEMBERDAYAAN KEGIATAN KEAGAMAAN DI KENAGARIAN) - Irwandi Irwandi; Novi Budiman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
The role of the ulema is very important in the development of the spiritual field, because they are the heirs of the prophet, so that the position and function of the ulama for Muslims are those who are followed by their steps, character and deeds and their opinions and approvals can be taken. Alim Ulama in the nagari government system has the authority and responsibility for the growth and development of activities that refer to the aqeedah, sharia, worship and religious social relations of the people. as a social organization engaged in the religious field. The Alim Ulama Nagari Elemental Institution is part of the Indonesian Ulema Council (MUI) organization. . The analysis used in this study is the data analysis of interactive model data analysis techniques. The approach used is a qualitative approach. The informants in this research were Wali Nagari, Management of Element Institutions, and Society. From this study, it was concluded that the existence of Islamic religious scholars in Pasie Laweh was set out in the form of a work program with four main activities, including education activities, Da'wah activities, Activities of Ta'rul Masjid Fields, and Worship Facility Infrastructure Activities, in carrying out these activities. there are still official factors such as the lack of commitment of the management in improving the quality of religious activities.